Analisis Penerapan Plan Maintenance System dan Pelatihan Terhadap Keselamatan Crew di Atas Kapal MV. Nadhif - Alfatihurrozaq, Visa Aditya; Indriyati, Retno; Wahyuni, Eni Tri (Majalah Ilmiah Gema Maritim, 2025)
This study aims to analyze how the implementation of the Plan Maintenance System (PMS) and safety training contribute to the preparedness of the MV Nadhif crew in facing emergencies. The research method used is descriptive qualitative, with data collection techniques through direct observation, interviews with five crew members, and documentation. The results of the study indicate that the PMS on the MV Nadhif has generally been implemented in accordance with procedures, especially for safety equipment such as lifeboats, fire extinguishers, and emergency pumps, although its implementation is still constrained by time and resources. Meanwhile, crew safety training such as fire drills and abandon ship drills are still not carried out regularly, only about once every six months. This lack of training frequency has an impact on the low preparedness of the crew in facing emergencies. Therefore, integration between a regular PMS system and routine safety training is needed to form an optimal work safety culture on board.